USE OF ARTIFICIAL BEE COLONIES ALGORITHM AS NUMERICAL APPROXIMATION OF DIFFERENTIAL EQUATIONS SOLUTION - Fahmi Fikri, Fariz
The differential equation is one of the branches in mathematics which is closely related to human life problems. Some problems that occur in our life can be modeled into differential equations as well as systems of differential equations. Therefore, solving a problem of differential equations is very important. Some differential equations are difficult to solve, so numerical methods are needed to solve that problems. Some numerical methods for solving differential equations that have been widely used are Euler Method, Heun Method, and others. While numerical method to solve system of differential equation which is often used that is ode45. However, some of these methods still have some restrictions that cause the method can not be used to solve more complex problems such as an evaluation interval that we can not change freely. New methods are needed to improve that problems. One of the method that can be used is the artificial bees colony algorithm. This algorithm is one of metaheuristic algorithm method, which can come out from local search space and do exploration in solution search space so that will get better solution than other method.